Large‐Ring Cyclodextrins as Chiral Selectors for Enantiomeric Pharmaceuticals. Issue 19 (1st April 2019) - Sonnendecker, Christian; Thürmann, Sebastian; Przybylski, Cédric; Zitzmann, Franziska D.; Heinke, Nicole; Krauke, Yannick; Monks, Kate; Robitzki, Andrea A.; Belder, Detlev; Zimmermann, Wolfgang
Abstract: Large‐ring cyclodextrins (CD) are cyclic glucans composed of 9 or more α‐1, 4‐linked glucose units. They are minor side products of bacterial glucanotransferases (CGTases, EC 2.4.1.19) and have previously been available only in very small amounts for studies of their properties in supramolecular complex formation reactions. We engineered a CGTase to synthesize mainly large‐ring CD facilitating their preparation in larger amounts. By reversed phase chromatography, we obtained single CD samples composed of 10 to 12 glucose units (CD10, CD11, and CD12) with a purity of >90 %. Their identity was confirmed by high resolution mass spectrometry and fragmentation analysis. We demonstrated the non‐toxicity of CD10–CD12 for human cell lines by a cell proliferation assay and impedimetric monitoring. We then showed that CD10 and CD11 are efficient chiral selectors for the capillary electrophoretic separation of the enantiomeric pharmaceuticals fluvastatin, mefloquine, carvedilol, and primaquine. Abstract : Large sugar rings : A novel strategy for the biocatalytic synthesis and purification allowed the efficient preparation of cyclodextrins composed of ten to twelve glucose units. Their non‐toxicity against human cell lines was demonstrated and cyclodextrins composed of 10 and 11 glucose units were shown to be efficient chiral selectors for the capillary electrophoretic separation of enantiomeric pharmaceuticals.